Pengaruh Corporate Social Responsibility (CSR) Terhadap Cost Of Equity Capital (CEC), Dengan Corporate Governance (CG) Sebagai Variabel Moderating (Studi Empiris Pada Seluruh Perusahaan Manufaktur yang tercatat di Bursa Efek Indonesia pada tahun 2010 sampai 2013). - Lamia, Lamia, Dra. Rina Trisnawati, AK,M.Si,Ph.D (2015)
The purposes of this study to get evidence The Effect OfCorporate Social Responsibility (CSR) To Cost Of Equity Capital (CEC),With Corporate Governance (Cg) As Moderating Variable (Empirical Studies In Manufacturing Companies At Indonesian Stock Exchange During 2010 - 2013 Period).The Proxies of Corporate Governance (CG) is institutional ownership, managerialownership,audit committee,composition of independent commissaries board and size of board commissaries moderating to disclosure corporate social responsibility to cost of equity capital. index CSR measured by GRI 2013 with 149 items. While, cost of equity capital measured EBO model which developed by Edwards and Bell (1961), Ohlson (1995), Feltham and Ohlson (1995) and Abarbanell and Bernard 91994) in Botosan and Plumlee (2000). Population of this research is all manufacture company in Indonesia Stock Exchange for 2010 - 2013 period, sample is 18 companies with 72 units analysis. This research uses MRA (Moderated Regression Analysis), with SPSS for Windows version 21.00 program. Resultof this research shows,CSR disclosureis not significantly influence to cost of equity capital. managerial ownership and the Size of board commissaries have are moderating CSR to cost of equity capital but institutional ownership,composition of independent commissaries board, and size of audit committee is not moderate CSR to cost of equity capital